2021
DOI: 10.1038/s41598-021-03440-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new scoring system for prognostic prediction of community-acquired pneumonia in older adults

Abstract: The discriminative power of CURB-65 for mortality in community-acquired pneumonia (CAP) is suspected to decrease with age. However, a useful prognostic prediction model for older patients with CAP has not been established. This study aimed to develop and validate a new scoring system for predicting mortality in older patients with CAP. We recruited two prospective cohorts including patients aged ≥ 65 years and hospitalized with CAP. In the derivation (n = 872) and validation cohorts (n = 1,158), the average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…In details, the AUC of the nomogram model was about 0.9 for predicting in-hospital mortality of CAP and observed to be higher than PSI, CURB-65 and qSOFA values (0.85, 0.86, and 0.71, respectively). Among them, the evidence for the application of 4 selected variables (Age, Pulse, NLR, and BUN) in our model has been supported by various studies ( 19 23 ). Here, we also reported that the addition of serum albumin (ALB) and D-dimer can improve the predictive ability for mortality of CAP in patients aged ≥ 65 years.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In details, the AUC of the nomogram model was about 0.9 for predicting in-hospital mortality of CAP and observed to be higher than PSI, CURB-65 and qSOFA values (0.85, 0.86, and 0.71, respectively). Among them, the evidence for the application of 4 selected variables (Age, Pulse, NLR, and BUN) in our model has been supported by various studies ( 19 23 ). Here, we also reported that the addition of serum albumin (ALB) and D-dimer can improve the predictive ability for mortality of CAP in patients aged ≥ 65 years.…”
Section: Discussionsupporting
confidence: 67%
“…In details, the AUC of the nomogram model was about 0.9 for predicting in-hospital mortality of CAP and observed to be higher than PSI, CURB-65 and qSOFA values (0.85, 0.86, and 0.71, respectively). Among them, the evidence for the application of 4 selected variables (Age, Pulse, NLR, and BUN) in our model has been supported by various studies (19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 57%
“…In one study, Sakakibara et al 35 established a new score model including albumin to predict severe adverse events (including death) in CAP patients, which exhibits a higher AUC value (0.85) compared with the other predictive models. Furthermore, another study by Shirata et al 25 developed another albumin-based system (using cutoff as 3.0 g/dL) to predict mortality in older patients with CAP, showing a higher AUC (0.809) than that of CURB-65. In addition, albumin decreased with aging for several potential reasons such as decline in cognition, poor oral health, and dysphagia 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Since Japan has one of the world’s highest life expectancies, it is likely that CURB-65 would not perform as well if applied to a Japanese cohort. Interestingly, CURB-65 also performs poorly when applied to Colombian patients (AUCs of 0.629-0.669 when tested against 3 cohorts) 20 . Hincapie suggested that this may be due to the factors underpinning a significant difference in community-acquired pneumonia-associated mortality (9.5% 17 versus 17-32% 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CURB-65 also performs poorly when applied to Colombian patients (AUCs of 0.629-0.669 when tested against 3 cohorts) 20 . Hincapie suggested that this may be due to the factors underpinning a significant difference in community-acquired pneumonia-associated mortality (9.5% 17 versus 17-32% 20 ). Although it has been suspected that this is the case, we note that biomarkers and prognostic scores developed in large multi-center trials in predominantly developed countries continue to be used in other countries and be incorporated into national guidelines without prior validation.…”
Section: Discussionmentioning
confidence: 99%